Swelling of clay minerals in unconsolidated porous media and its impact on permeability. (September 2015) - Aksu, I.; Bazilevskaya, E.; Karpyn, Z.T.
Graphical abstract: Abstract : Highlights: Clay swelling was quantified by X-ray micro-computed tomography. Swelling coefficient was used to model permeability reduction in natural samples. The effect of swelling clays on permeability reduction depends on the matrix grain size. Abstract: This work combines core-flood experiments with X-ray μ-computed tomography (μ-CT) to investigate the swelling of clay minerals and its impact on permeability of unconsolidated porous media. Both swelling (montmorillonite) and non-swelling (kaolinite) clay were added as coatings on soda lime beads and quartz grains. Clay content varied from 1.4 to 5.5 wt.% in the montmorillonite-coated samples and from 2.0 to 6.8 wt.% in the kaolinite-coated samples. Permeability changes were monitored as a function of time using pure water. Visualization of coated bead and grains columns by μ-CT provided quantitative information on morphological changes of clay grains/coatings among dry and water-saturated samples. All clay-coated samples showed a 10–40% decrease in permeability as compared to uncoated samples. In general, permeability decreases with increasing clay content. A 39% volume increase of montmorillonite particles was observed by μ-CT immediately after the sample was saturated with water, i.e. swelling occurred almost instantaneously after water–clay contact. In contrast, kaolinite particles had a 15% volume increase, which was primarily attributed to the hydration of clay pellets by water. The calculated porosity reduction associated with clay swelling ranged from 0.4% to 1.7% including both montmorillonite- and kaolinite-coated samples. This decrease in porosity was estimated to cause only a 2–5% reduction in permeability, primarily due to the high initial porosity and permeability of the selected samples. This study presents a baseline to estimate changes in permeability as a result of clay swelling for samples with variable clay content, grain size, and porosity.